PENEGAKAN HUKUM TERHADAP ANAK YANG MENJADI KORBAN KEKERASAN DALAM RUMAH TANGGA BERDASARKAN UNDANG-UNDANG NO. 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NO. 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK (STUDI KASUS : PUTUSAN NO. 322/Pid.Sus/2014/Pn.Jkt.Tim) - Andreas Eka Prasetya; Mariduk Leonardo Aritonang (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
The child is a mandate as well as a gift from God Almighty, even the child is considered as the most valuable asset compared to other assets. Thus, children must always be protected and protected because in their children the inherent dignity, dignity and rights of a child must be upheld. However, in reality children often become victims of violence, especially domestic violence. This is found in decision No.322 / Pid.Sus / 2014 / PN.Jkt.Tim. In this ruling, child abuse was committed by his father to his own child. violence happened because his father was upset about his son because his son was often sick and troubled the father.The method used in this study is normative juridical legal research. Normative juridical legal research is research based on literature taken from library materials or document studies, carried out in an effort to obtain the necessary data related to the problem. The data used is secondary data consisting of primary legal materials and secondary legal materials. For data analysis performed with qualitative juridical analysis method. Regarding the consideration of the judges Case Number: 322 / Pid.Sus / 2014 / PN.Jkt.Tim, dated June 24, 2014, these considerations have been proven by using Article 44 paragraph (1) of Law Number 23 of 2004 concerning Elimination of Domestic Violence Stairs. However, as a result of this decision there were still many violence against children that occurred in the surrounding environment, especially the family environment and did not give a sense of deterrent effect on the perpetrators.From the decision analysis, it can be seen that the application of Article 44 paragraph (1) of Law Number 23 of 2004 concerning the Elimination of Domestic Violence as the basis of the Public Prosecutor's indictment is deemed weak in an effort to protect the interests of children's rights and rights.Child protection as a victim of criminal acts will be more equitable if the charges are prepared using Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection because it provides protection for children's interests and rights while providing a sense of deterrent effect optimal for the perpetrator / defendant and threatens to punish the perpetrator / defendant more severely